The contribution of stress in pathogenesis of acne - Rokowska-Waluch, Anita; Cybulski, Marcin; Żurawski, Jakub; Mojs, Ewa; Pawlaczyk, Mariola (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction . Chronic psychological stress is an important factor of acne pathogenesis, and the mental stress induced by acne causes emotional and social problems. Negative psychological effects of acne are: anxiety, depression, reduction in social functioning and decreased quality of life. Objective . To evaluate the correlation between acne severity and intensity of psychological stress, to compare the intensity of psychological stress in acne patients and healthy volunteers, and to compare the methods of coping with stress in both groups. Material and methods . The study group consisted of 76 acne patients: 18 men and 58 women, aged from 18 to 34 years. 40 healthy volunteers (18 men and 22 women aged from 20 to 34 years) served as the control group. Psychological stress was analysed using the Social Readjustment Rating Scale (SRRS), whereas the methods of coping with stress were assessed with the Coping Inventory for Stressful Situations (CISS). The results were analysed statistically using PASW Statistics SPPS v. 20. Results. There was no statistically significant difference between the clinical state and the intensity of stress in the patient group. The evaluation of methods of coping with stress showed a significantly higher rate for avoidance-oriented coping among acne patients. Conclusions . The number of stressful events is not a factor determining the severity of acne. The risk of a psychosomatic disease and its severity may depend on tolerance of stress and methods of coping with stress.